Immigrant selection before and after communism1. Issue 4 (22nd July 2018) - Ganguli, Ina
Abstract: The end of the Soviet Union and communist regimes throughout Eastern Europe led to sudden increases in emigration and large changes in wage inequality. This has provided a unique opportunity to understand how these changes altered incentives to emigrate during the transition period. In this paper, I analyze immigrant selection before and after the fall of the Soviet Union within a Roy Model framework, in which the relative return to skills determines the skill composition of immigrants. Using micro‐level data from Russia, Ukraine and Bulgaria, matched to Census data on immigrants from these countries in the United States, Spain and Greece in the post‐Soviet period, I find evidence of positive selection of immigrants in the US, and negative selection for Greece and Spain. Using retrospective data from Ukraine during the communist period, I find that selection among Soviet men in the US was intermediate and selection among women was positive.